Pengaruh Karir Obyektif Pada Wanita Terhadap Konflik Keluarga-Pekerjaan Kasus Pada Universitas Muhammadiyah Surakarta - Kussudyarsana Kussudyarsana (Benefit: Jurnal Manajemen dan Bisnis, 2009)
This research due to test influence of  objective career at woman toward level of  work family conflict. To answer research question, we investigate 51 both of  woman lecturer and officer  that work in university of Muhammadiyah Surakarta, and comparing different  career objective. The one group was people  that occupy  leader in certain job and the other group was member of  certain departmen. To analyze  research question, we use independent t test, and regrresion analysis with dummy variable.  The result suggested there are no  impact of objective career toward level of conflict. All of hyphotesis testing not confirm to the empirical data.